Anti-inflammatory and Anti-snake Venom Activity of Andrographis stenophylla Leaf - THANGAVEL, NEELAVENI; KUMAR GUPTA, JAYANTA (Asian Journal of Chemistry, 2010)
In the present study, the anti-inflammaotry and anti-snake venom properties of methanol extract of Andrographis stenophylla leaf was investigated. The anti-inflammatory activity was checked using carrageenan-induced acute pedal paw edema model and freund’s complete adjuvant induced chronic inflammatory moel. In both acute and chronic inflammatory models, the extract exhibited significant anti-inflammatory activity at two doses of 50 and 100 mg/kg. The methanol extract of Andrographis stenophylla leaf, also effectively neutralized Naja najanaja venom induced lethal, cardiotoxic, neurotoxic and hemorrhagic effects. The leaf extract was found to potentiate the polyvalent snake venom antiserum action in experimental animals. The extract provides a 3.5 fold protection against the lethal effect of venom and 350 fold potentiation of anti serum action. The plant possesses significant antiinflammatory and anti-snake venom activity and the work provides pharmacological evidence for the folklore claim of anti-snake venom activity.